Localization of the Sensory Neurons and Mechanoreceptors Required for Stretch-Evoked Colonic Migrating Motor Complexes in Mouse Colon - Zagorodnyuk, Vladimir P.; Spencer, Nick J. (Frontiers in Physiology, 2011)
The pacemaker and pattern generator that underlies the cyclical generation of spontaneous colonic migrating motor complexes (CMMCs) has recently been identified to lie within the myenteric plexus and/or muscularis externa. Neither the mucosa, nor the release of substances from the mucosa were found to be required for the spontaneous generation of CMMCs. However, it is known that stretch applied to the colonic wall can also evoke CMMCs and since stretch of the gut wall is known to stimulate the mucosa, it is not clear whether release of substances from the mucosa and/or submucosal plexus are required for stretch-evoked CMMCs. Therefore, the aim of this study was to determine whether circumferential stretch-evoked CMMCs require the presence of the mucosa and/or submucosal plexus in isolated mouse colon. Spontaneous CMMCs were recorded from full length sheet preparations of colon in vitro. Graded circumferential stretch (at a rate of 100μm/s) applied to a 15mm segment of mid-distal colon reliably evoked a CMMC, which propagated to the oral recording site. Sharp dissection to remove the mucosa and submucosal plexus from the entire colon did not prevent spontaneous CMMCs and circumferential stretch-evoked CMMCs were still reliably evoked by circumferential stretch even at lower thresholds. In contrast, in intact preparations, direct stimulation of the mucosa (without accompanying stretch) proved highly inconsistent and rarely evoked a CMMC. These observations lead to the inescapable conclusion that the sensory neurons activated by colonic stretch to initiate CMMCs lie in the myenteric plexus, while the mechanoreceptors activated by stretch, lie in the myenteric ganglia and/or muscularis externa. Stretch activation of these mechanoreceptors does not require release of any substance(s) from the mucosa, or neural inputs arising from submucosal ganglia.